2021
DOI: 10.1200/jco.21.00976
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Postoperative Trial of Platinum-Based Chemotherapy Versus Capecitabine in Patients With Residual Triple-Negative Breast Cancer Following Neoadjuvant Chemotherapy: ECOG-ACRIN EA1131

Abstract: PURPOSE Patients with triple-negative breast cancer (TNBC) and residual invasive disease (RD) after completion of neoadjuvant chemotherapy (NAC) have a high-risk for recurrence, which is reduced by adjuvant capecitabine. Preclinical models support the use of platinum agents in the TNBC basal subtype. The EA1131 trial hypothesized that invasive disease-free survival (iDFS) would not be inferior but improved in patients with basal subtype TNBC treated with adjuvant platinum compared with capecitabine. PATIENTS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 39 publications
4
105
0
Order By: Relevance
“…Patients assigned to carboplatin on BrighTNess had a larger absolute increase in pCR rate than on CALGB 40603 (27% v 13%) 27 and in results presented at the 2021 ESMO Congress, had significantly better 4-year EFS and a trend toward improved OS 31 although other factors might have contributed to these apparent discrepancies. Although EA1131 failed to demonstrate noninferiority of adjuvant platinum therapy compared with capecitabine in patients with TNBC with RD after (non–platinum-containing) NACT, 32 no randomized trial has reported on the addition of carboplatin to adjuvant chemotherapy for TNBC; however, one is ongoing (NRG-BR003).…”
Section: Discussionmentioning
confidence: 99%
“…Patients assigned to carboplatin on BrighTNess had a larger absolute increase in pCR rate than on CALGB 40603 (27% v 13%) 27 and in results presented at the 2021 ESMO Congress, had significantly better 4-year EFS and a trend toward improved OS 31 although other factors might have contributed to these apparent discrepancies. Although EA1131 failed to demonstrate noninferiority of adjuvant platinum therapy compared with capecitabine in patients with TNBC with RD after (non–platinum-containing) NACT, 32 no randomized trial has reported on the addition of carboplatin to adjuvant chemotherapy for TNBC; however, one is ongoing (NRG-BR003).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the addition of capecitabine, lymph node positive and adjuvant chemotherapy were beneficial for DFS, which might be related to the anti-angiogenesis of capecitabine and the inhibition of tumor immune escape ( Pasquier et al, 2010 ). The ECOG-ACRIN EA1131 trial compared the effects of platinum preparations and capecitabine after neoadjuvant chemotherapy ( Mayer et al, 2021 ). The results showed that there was no significant difference between the effects of platinum preparations and capecitabine, and platinum preparations brought more serious toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, platinum agents did not improve the 3-year iDFS in patients with basal subtype TNBC compared with capecitabine (42% vs 49%); additionally, grade 3-4 toxicities were more common in the platinum-arm. 72 These studies generally show that adjuvant capecitabine has activity in TNBC when used as an adjunct after standard anthracycline/taxane chemotherapy, but that there is no benefit in biologically unselected patients. Though the CIBOMA/GEICAM did achieve a significant OS benefit in non-basal-like TNBC, current clinical practice does not discriminate between basal and non-basal TNBC, so the results of this trial are difficult to apply in practice.…”
Section: Predictive Biomarkers Of Response To Nact In Tnbcmentioning
confidence: 99%